Identifikasi Komponen Daya Tarik Wisata Dan Pengelolaan Pantai Labuan Sait, Desa Adat Pecatu, Kabupaten Badung - Putra, Putu Karyana; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p13, 2019)
The management is one of the supporting activities in tourism. Management is the key of how an expanded appeal or not. Labuan Sait Beach has the potential of nature in the form of a white-sand beach and good waves for surfing. The assumption behind this is based on the dipilhnya coast of Labuan Sait as a research topic in order to find out the components of a tourist attraction and how it managed.      The research methodology used in this study is a qualitative research, with observation, in-depth interviews, documentation, and research studies as well as using the concept of tourist attraction,  tourism potentital and management.      The results of this research shows that the tourist attraction of the Labuan Sait Beach  was established as a new tourist attraction on March 1, 2016 and the enforcement of admission for tourists. Attraction of the Labuan Sait Beach is managed by the Pecatu Village goverment and Uluwatu attraction management.   Keywords : management, tourism potential, tourist attraction, Labuan Sait Beach